COLLECTORS’ PICKS: MAPPING THE MOST POPULAR VINTAGE AUDIO COMPONENTS AMONG VINTAGE ENTHUSIASTS (Proceeding of the International Conference on Arts and Humanities, 2024)
The soft hum of vintage amplifiers, the subtle crackle of vinyl spinning on turntables, and the warm glow of analog nostalgia are the snapshots of a growing movement that's captivating music enthusiasts worldwide. In the current digital age, there's a turning back the clock to embrace the tangible, the analog, and the soulful sound of vintage audio equipment. There is a community of diverse individuals, from seasoned audiophiles to curious newcomers, drawn together not by the latest technology, but by the allure of decades-old components. It is not merely about collecting artifacts but about joining a cultural revival that's gaining momentum. Not to forget nostalgia plays a significant role in their preferences, with a desire to recapture memories, embrace historical charm, and connect with the past. Hence, this paper examines vintage audio components that vintage enthusiasts love to gather the most in building their vintage audio collections. This study implemented a qualitative approach using self-administered questionnaires involving a total of 48 Malaysian listeners aged between 18 to 56 years old and owned the vintage audio. The data was analyzed to identify common themes and patterns regarding the popularity of vintage components among vintage enthusiasts in Malaysia. The data indicates that the most commonly collected vintage audio components among Malaysian vintage enthusiasts are amplifiers or receivers, turntables, and speakers/speaker systems. This paper contributes to the literature by expressing a deeper understanding of the local vintage audio landscape and offering practical implications for businesses and manufacturers seeking to cater to the unique tastes and desires of vintage enthusiasts in Malaysia. By tapping into the appeal of vintage audio components, companies can create products and marketing strategies that stand out in the market and resonate with consumers on a deeper level.
Keywords: vintage; audio components; collection; vintage enthusiast; Malaysia